Cytomegalovirus‐related sepsis‐like syndrome in very premature infants in Japan. Issue 1 (21st March 2022) - Namba, Fumihiko; Nakagawa, Ryota; Haga, Mitsuhiro; Yoshimoto, Seiji; Tomobe, Yutaro; Okazaki, Kaoru; Nakamura, Kenji; Seki, Yoshiko; Kitamura, Souya; Shimokaze, Tomoyuki; Ikegami, Hitoshi; Nishida, Kosuke; et al.
Abstract: Background: Very premature infants are at high risk of developing a symptomatic postnatal cytomegalovirus (CMV) disease, such as CMV‐related sepsis‐like syndrome (CMV‐SLS). To address the limited data regarding its clinical features, a nationwide survey of CMV‐SLS was conducted. Methods: A questionnaire regarding CMV status and the clinical outcomes of CMV‐SLS was sent to centers with reported cases of CMV‐SLS. Results: Twelve CMV‐SLS cases, nine confirmed and three probable cases, were reported during the 3‐year survey period. The median gestational age and birthweight were 25 weeks and 547 g, respectively. At disease onset, the median age was 49 days, and the corrected age was 31 weeks. Untreated breast milk was given in four cases (33%), whereas frozen breast milk was given in nine (75%). No specific symptoms and laboratory data regarding CMV‐SLS were found. Conclusions: Very premature infants developed CMV‐SLS after 1 month of age. There are no symptoms and signs specific for the diagnosis of CMV‐SLS, so CMV‐SLS should be considered as a differential diagnosis for premature infants who have unexplained sepsis‐like symptoms during the convalescent phase.